STRATEGIES FOR DEVELOPING STUDENTS’ INFORMATION CULTURE IN THE CONTEXT OF DIGITAL TRANSFORMATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
. The rapid advancement of digital technologies has significantly transformed educational systems worldwide, creating both opportunities and challenges for higher education institutions. In the digital era, students are constantly exposed to vast amounts of information originating from diverse digital sources, including online databases, social media platforms, educational technologies, and artificial intelligence systems. Consequently, the development of information culture has become an essential component of professional and personal competence. Information culture encompasses a set of knowledge, skills, values, and attitudes that enable individuals to effectively search, evaluate, process, communicate, and ethically use information.
Keywords: Digital transformation has become one of the most influential global trends affecting economic, social, cultural, and educational development. The integration of digital technologies into educational environments has fundamentally changed the ways information is created, accessed, distributed, and utilized. Higher education institutions increasingly rely on digital platforms, cloud technologies, artificial intelligence applications, virtual learning environments, and online communication tools to facilitate teaching and learning processes (OECD, 2023).